Problem :

A circle touches the parabola $y^2=4ax$ at P. It also passes through the focus S of the parabola and intersects its axis at Q. If angle SPQ is $\frac{\pi}{2}$ find the equation of the circle.

Solution :

Let the point P ($at^2,2at)$ If the circle touches the parabola $y^2=4ax$ at $ P (at^2,2at)$ , they must have a common tangent at that point, and hence a common normal. The centre of the circle must lie on that normal. Let $(h,k)$ be the coordinates of the centre and r be the radius of the circle.

Then its equation can be written as $x^2+y^2-2hx-2ky+c=0......(i)$

The equation to the normal at $(at^2,2at)$ is $y=-tx +2at +at^3 ......(ii)$

As the centre $(h,k)$ lies on the normal (ii) , hence $k =-th +2at +at^3$....(iii)

Focus of the parabola is $(a,0)$ As the circle passes through (a,0) and $(at^2,2at)$ the distance of these points from the centre (h,k) must each be equal to the radius. so $r^2=(h-a)^2+k^2= (h-at^2)^2 +(k-2at)^2$

or $-2ah +a^2=-2aht^2-4akt+a^2t^4+4a^2t^2$

or $4kt =h(1-t^2)+at^4 +4at^2-a$.....(iv)

Solving (iii) and (iv) , $2h= a(3t^2+1) .....(v) $ and $2k =a(3t-t^3).....(vi)$

Putting the values of h and k in (i) we get the equation of the circle $x^2+y^2-a(3t^2+1)x -a(3t-t^3)y+c=0$ .....(vii) As this circle passes through the focus (a,0) the coordinates will satisfy it :

Therefore, $a^2-a^2(3t^2+1)+c=0$ $\therefore c =3a^2t^2$

Putting this value of c in (vii) the circle is $x^2+y^2-ax(3t^2+1)-ay(3t-t^3)+3a^2t^2=0$

But I am unable to get the equation of the circle which is $x^2+y^2-10ax +9a^2=0$ Please help . Thanks.


Since $S$ and $Q$ are on the parabola's axis and $\angle{SPQ}=\frac{\pi}{2}$, we can say that the line segment $SQ$ is the diameter of the circle, which means the center of the circle is on the parabola's axis.

Hence, you'll get $k=0\Rightarrow t^2=3$.

| cite | improve this answer | |

The centre of the circle is $T=(b,0)$. We know the normal line at $P$ on both the circle and parabola points to it. $P=(a t^2, 2 a t)$ as above on $y^2=4 a x$. The radius of the circle is ST and has length $b-a$. So the equation is $(x-b)^2+y^2=(b-a)^2$.

$P$ is on the circle, $(a t^2-b)^2+(2 a t)^2=(b-a)^2$ which simplifies to: $(a^2(t^2+(2-c))^2+6c-5-c^2)=0$, where $c=\frac{b}{a}$.

$PT \cdot \text{tangent} =0=[at^2-b,2at]\cdot [2at,2a]=(at^2-b)2at+4a^2t=a^2t(t^2-c+2)$ which means $6c-5-c^2=0$ which has solutions $c=1$ or $c=5$.

Putting it all together $(x-5a)^2+y^2=(4a)^2$.enter image description here

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.